2015
DOI: 10.1161/circulationaha.114.013789
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Hypertrophic Preconditioning Attenuates Cardiomyocyte Hypertrophy and Slows Progression to Heart Failure Through Upregulation of S100A8/A9

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 62 publications
(59 reference statements)
0
58
0
2
Order By: Relevance
“…At present, the methods of enhancing the anti‐OS ability of BMSCs mainly include the application of antioxidants or drugs, which mainly play a role through intervention of the signaling pathways of aging and apoptosis, but the effect is limited . Clinically, we often find that preconditioning has protective effects on organisms or body, such as myocardial ischemic preconditioning . That being so, whether OS preconditioning can also enhance anti‐OS ability of BMSCs, protect the survival of BMSCs under OS conditions?…”
Section: Introductionmentioning
confidence: 99%
“…At present, the methods of enhancing the anti‐OS ability of BMSCs mainly include the application of antioxidants or drugs, which mainly play a role through intervention of the signaling pathways of aging and apoptosis, but the effect is limited . Clinically, we often find that preconditioning has protective effects on organisms or body, such as myocardial ischemic preconditioning . That being so, whether OS preconditioning can also enhance anti‐OS ability of BMSCs, protect the survival of BMSCs under OS conditions?…”
Section: Introductionmentioning
confidence: 99%
“…The cellular hypertrophic response in cardiac myocytes appears to be an adaptational event and is well recognized to be responsible for several cardiovascular diseases such as heart failure and hypertrophic cardiomyopathy [25,26]. Ang II, one of the most common causes of myocardial hypertrophy, also plays a major role in the progression of myocardial hypertrophy to heart failure through signal transduction [1,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of the calcineurin/NFAT pathway by S100A8/A9 moderately causes the cardiac protection of hypertrophic preconditioning. 88 It has been reported that inhibition of nuclear factor (NF-kappa B) accenuates the cardio protective effect of ischemic preconditioning and reduces the infarct size during reperfusion. 89 Conversely, other have hypothesized that NF-kappa B have necessary and essential role in the development of compensatory and adaptive hypertrophy and its absence accelerates the remodeling process and functional development of heart failure.…”
Section: Impact Of Cardiac Hypertrophy On Ischemic Preconditioning Anmentioning
confidence: 99%